2023
DOI: 10.58934/jgeb.v4i13.143
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetry effect of budget deficit and inflation in Nigeria

Abstract: This study evaluates the asymmetry effect of budget deficit and inflation in Nigeria spanning 1986 and 2020. The dissertation employed the Non-linear Autoregressive Distributed Lag (NARDL) approach of Shin, Yu and Greenwood-nimmo (2014) to examine the effect of budget deficit on inflation in Nigeria. The study employed annual data on budget deficit (proxied by budget deficit as a share of GDP), money supply (proxied by money supply), inflation (proxied by consumer price index) collected from Central Bank of Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In most developed countries, the rate of inflation is managed to a one-digit rate; however, in developing countries like Nigeria, it is mostly in two digits. Some recent studies have confirmed that Nigeria has a high rate of inflation and found different impacts of inflation; although, they have not considered inflation hedging capabilities [14][15][16][17]. During periods of inflation, the prices of goods and services increase as it also erodes people's purchasing power.…”
Section: Introductionmentioning
confidence: 99%
“…In most developed countries, the rate of inflation is managed to a one-digit rate; however, in developing countries like Nigeria, it is mostly in two digits. Some recent studies have confirmed that Nigeria has a high rate of inflation and found different impacts of inflation; although, they have not considered inflation hedging capabilities [14][15][16][17]. During periods of inflation, the prices of goods and services increase as it also erodes people's purchasing power.…”
Section: Introductionmentioning
confidence: 99%